Performing Hysteria Images and Imaginations of Hysteria - Braun, Johanna (Leuven University Press, 2020)
"We seem to be living in hysterical times. A simple Google search reveals the sheer bottomless well of "hysterical" discussions on diverse topics such as the #metoo movement, Trumpianism, border wars, Brexit, transgender liberation, Black Lives Matter, COVID-19, and climate change, to name only a few. Against the backdrop of such recent deployments of hysteria in popular discourse--particularly as they emerge in times of material and hermeneutic crisis--Performing Hysteria re-engages the notion of "hysteria". Performing Hysteria rigorously mines late 20th- and early 21st-century (primarily visual) culture for signs of hysteria. The various essays in this volume contribute to the multilayered and complex discussions that surround and foster this resurgent interest in hysteria--covering such areas as art, literature, theatre, film, television, dance; crossing such disciplines as cultural studies, political science, philosophy, history, media, disability, race and ethnicity, and gender studies; and analysing stereotypical images and representations of the hysteric in relation to cultural sciences and media studies. Of particular importance is the volume's insistence on taking the intersection of hysteria and performance seriously."